2020
DOI: 10.1186/s12936-020-03191-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the capacities of community health workers mobilized for seasonal malaria chemoprevention in Burkina Faso

Abstract: Background: Seasonal malaria chemoprevention (SMC) relies on community health workers to distribute drugs. This study assessed: (1) the capacity of community-based distributors (CBDs) at the start and end of a campaign and from one campaign to another after training or refresher courses before each round; (2) to what extent CBDs' experience over several campaigns contributed to measurable increase in their capacities; and (3) to what extent the training and experience of committed CBDs helped the less producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, the annual recruitment process causes disruption and poses risks to sustainability of the strategy. Concerns about annual recruitment of LMs are similar to those raised in a study of retention of community-based SMC staff in Burkina Faso [ 15 ]. It is recognized that when staff are retained and able to work in successive campaigns, they have a better understanding of their role and this is something future SMC campaigns in Kano state and other areas where SMC campaigns are implemented should aim for.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, the annual recruitment process causes disruption and poses risks to sustainability of the strategy. Concerns about annual recruitment of LMs are similar to those raised in a study of retention of community-based SMC staff in Burkina Faso [ 15 ]. It is recognized that when staff are retained and able to work in successive campaigns, they have a better understanding of their role and this is something future SMC campaigns in Kano state and other areas where SMC campaigns are implemented should aim for.…”
Section: Discussionmentioning
confidence: 79%
“…As argued by others, there should be a careful consideration of the practical implications of introducing additional roles for community health workers and volunteers, including concerns about workload, costs and training requirements [ 22 ]. Programme planners and policy makers need to discuss with key stakeholders about the feasibility and best modalities for introducing these new roles for LMs within SMC campaigns, especially since previous research cautions against adding new roles for community level SMC staff [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding training, a longitudinal study in Burkina Faso found that capacities of community distributors grew from round to round and campaign to campaign, after most had undergone training and been supervised. 42 However, in the context of Chad, retaining community distributors is a challenge since as many of them are students; at cycle 3, most of them leave villages for school or become preoccupied with their studies. Therefore, health centers need to reconsider the timing of training.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since the WHO recommendation was made, implementation studies have been conducted in Sahelian and sub-Sahelian regions such as The Gambia, Chad, Burkina Faso, Mali and Senegal, which con rmed the effectiveness and cost-effectiveness of SMC in real-world conditions. [3][4][5][6][7][8][9] For those reasons, the scale-up of SMC in West and Central Africa is often seen as a success story. East and Southern African regions were not prioritized for SMC scale-up due to high levels of SP resistance.…”
Section: Introductionmentioning
confidence: 99%